2020
DOI: 10.1039/c9ew00606k
|View full text |Cite
|
Sign up to set email alerts
|

A review of the treatment of low–medium strength domestic wastewater using aerobic granulation technology

Abstract: In recent times, the treatment of actual low-medium strength domestic wastewater using aerobic granulation has been proposed as a promising alternative to replace the conventional activated sludge system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 120 publications
0
11
0
Order By: Relevance
“…Instead, typical ratios of SVI 30 /SVI 10 were found to be in the range of 0.85–1.0, representing a good granulation rate in the granulation system, particularly for the treatment of domestic wastewater. 10 Based on Fig. 4(b), SVI 30 /SVI 10 values of 0.82 ± 0.04, 0.89 ± 0.04 and 0.75 ± 0.02 were observed during M1, M2 and M3, respectively.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Instead, typical ratios of SVI 30 /SVI 10 were found to be in the range of 0.85–1.0, representing a good granulation rate in the granulation system, particularly for the treatment of domestic wastewater. 10 Based on Fig. 4(b), SVI 30 /SVI 10 values of 0.82 ± 0.04, 0.89 ± 0.04 and 0.75 ± 0.02 were observed during M1, M2 and M3, respectively.…”
Section: Resultsmentioning
confidence: 85%
“…9 According to We et al (2020) and Layer et al (2021), the formation of anaerobic/anoxic zones within the aerobic granules is governed by oxygen utilisation in the upper layers of the aerobic granules, which subsequently creates an oxygen gradient within the aerobic granules. 9,10 Under a constant dissolved oxygen (DO) operation of the SBR, the oxygen gradient established across the layers of aerobic granules is closely related to the granule size. 9 The formation of larger diameter granules is crucial in prolonging the anaerobic/anoxic zone duration inside the granules.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table S1, the TOC, COD, and BOD 5 of the NF concentrate were 65 ± 5 mg/L, 235 ± 35 mg/L, and 3.2 ± 0.4 mg/L, respectively. Based on the reported typical composition of untreated domestic wastewater and the TOC and COD values measured here, the untreated NF concentrate can be categorized as low-strength wastewater . The BOD 5 /COD ratio was calculated to be 0.014 ± 0.003, which indicated that the NF concentrate was unsuitable for biological treatment .…”
Section: Resultsmentioning
confidence: 88%
“…Based on the reported typical composition of untreated domestic wastewater and the TOC and COD values measured here, the untreated NF concentrate can be categorized as low-strength wastewater. 62 The BOD 5 / COD ratio was calculated to be 0.014 ± 0.003, which indicated that the NF concentrate was unsuitable for biological treatment. 63 The low biodegradability of the NF concentrate is reasonable as the concentrate was produced following treatment by a biological process.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of the advantages of aerobic granular technology, shortage and complexity of substrate associated with low wastewater cause undesirable granular biomass growth. Also, limited research was applied to treat low wastewater, especially in a full-scale plant using aerobic granular technology yet (We et al, 2020 ). Using granular aerobic sludge technology in existing conventional activated sludge plants is facing the squandering of putting aside both primary and final settling tanks, in addition to the small size of the aeration basin, which isn’t valid to longer operation in sequencing batch reactor mode (Nancharaiah & Reddy, 2018 ).…”
Section: Introductionmentioning
confidence: 99%